Pengaruh angka harapan hidup, rata-rata lama sekolah dan pengeluaran perkapita terhadap tingkat kemiskinan pada Kabupaten /Kota di Provinsi Jambi - Ropikatul Hasanah; Syaparuddin Syaparuddin; Rosmeli Rosmeli (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
This study aims to analyze the development of life expectancy, the average length of schooling, expenditure per capita, and poverty level in districts/cities in Jambi Province, as well as analyze the effect of life expectancy, the average length of schooling, and expenditure per capita on poverty levels. The analytical method used is panel data regression. The results of this study indicate that. After the Chow and Hausmant test, the best model is the Fixed effect. Partially, the analysis results of the variable life expectancy and expenditure per capita significantly impact the poverty level. At the same time, the average length of school does not have a significant effect. Simultaneously, life expectancy, the average schooling size, and per capita expenditure significantly impact poverty levels in districts/cities in Jambi province Keywords: Poverty, Life expectancy, Length of schooling, Expenditure per capita